Global trends in business tourism research - Hernández-Andrés, Víctor; de Frutos Madrazo, Pablo; Frechoso Remiro, Juan Carlos; Martín-Cervantes, Antonio (Turyzm/Tourism, 2025)
Business tourism is a key economic driver in the regions where it is present. In recent decades, the remarkable growth of academic research both in quantity and diversity of articles, makes it necessary to structure and organize this segment of tourism to identify trends in the sector and facilitate the work of the community in the research process. Using Scopus as a bibliographic database, this article performs a systematic analysis of the academic research that has addressed business tourism in the period from 1970 to 2021. Through a robust methodological approach that includes the use of bibliometric tools, the study analyzes data to identify patterns, key actors and emerging trends in the field. It examines the main research trends and provides an analysis through strategic diagrams of the keywords found in business tourism which has not been done to date. The main findings confirm the consolidation of academic research in the meetings industry over the past two decades. We also identify the main trends, including the progressive integration of its activities in line with sustainable development criteria, the use and integration of new technologies, and the increasing need for professionalization in a growing sector.